COMMUNICATIVE APPROACH TO TEACHING ENGLISH IDIOMS (Proceedings of International Educators Conference, 2024)
Communicative language teaching methods (CLT) are commonly considered as an effective approach in developing students' communicative competence and communication skills. It emphasizes real-life experience and focuses on developing learners' ability to use language in authentic contexts. Idioms are an essential conversational component in each language, and reflect the long history of the language development. Knowledge of idioms as specific reproducible set expressions in the vocabulary is very significant because they often encapsulate a nationally specific cultural outlook, and demonstrate the level of the advanced mastering of the foreign language.